EMPLOYEES PERCEPTION TOWARDS TALENT MANAGEMENT STRATEGY AND STAFF RETENTION AT DELOITTE & TOUCHE, KENYA - Mitambo, Freda Muchena; Ndemo, Prof. Bitange (Journal of Strategic Management, 2016)
Purpose: The purpose of the study was to find out the perceptions of employees towards talent management strategy and staff retention at Deloitte & Touche, Kenya. Methodology: This study has adopted the form of a descriptive survey design. The population that was targeted for the study was the 400 employees that work in Deloitte Kenya offices. Therefore the sample size was 80 employees who were at the offices of Deloitte Kenya, who were selected using stratified random sampling which was done using R software. The study made use of primary data that was collected through the use of a questionnaire. Descriptive statistics which include mean and frequencies have been used for the purpose of performing data analysis. The mean scores have been used to rate the factors in order of their importance. After data collection which was carried out through the use of questionnaires, this data was prepared for purposes of analysis by having it edited, sorting out any blank responses that were noted, coding these responses, categorizing it as well as keying it into the statistical package for social sciences (SPSS) software so as to be able to analyse it. Results: The study found thatremuneration, training and career development; organizational culture, reward and recognition all have a significant and positive association with staff retention. Unique contribution to theory, practice and policy: The study recommends that both benefits and salaries of employees should be commensurate according to the efforts. In addition the bonus pay to employees should be structured in a manner to motivate employees. This will help in improving employee retention.